2022
DOI: 10.3390/agronomy12081738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Desired-Genetic-Gain Selection Indices in Late Generations as an Insight on Superior-Family Formation in Bread Wheat (Triticum aestivum L.)

Abstract: Wheat is one of the most important sources of food worldwide. A selection index helps in making selection decisions and permits the exploitation of information on correlated traits to improve yields. Two cycles of pedigree selection based on the desired-genetic-gain selection index were imposed to identify the best index to isolate promising lines. The base population was composed of 120 families of bread wheat in the F6 generation. Eight combinations were constructed from six traits, i.e., days to heading (DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The F2 lines possibly maintain photosynthesis, chlorophyll content, and membrane stability under waterlogging conditions (Kumar et al, 2013). Moreover, the 20 F2 lines were selected for the next breeding program by the selection intensity from selecting 10% of superior plants (Ejara et al, 2016;Mahdy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The F2 lines possibly maintain photosynthesis, chlorophyll content, and membrane stability under waterlogging conditions (Kumar et al, 2013). Moreover, the 20 F2 lines were selected for the next breeding program by the selection intensity from selecting 10% of superior plants (Ejara et al, 2016;Mahdy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the complicated, polyploid wheat genome, selecting for these mutations is very difficult. Hundreds of yield-related quantitative trait loci (QTL) have been identified by molecular markerbased genetic mapping; several of these QTL have been cloned in species with smaller genomes, such as rice [16]. Direct cloning of yield-related genes in wheat and barley using techniques of gene high-resolution mapping and map-based cloning remains very difficult due to the complexity of the genomes.…”
Section: Methods For Identifying the Main Genes That Determine Yieldmentioning
confidence: 99%
“…These authors also showed that SHI and WI indices produced better performance when used to select important characteristics of bread wheat, without significant gain loss in the main trait. In another study, Mahdy et al (2022) showed good results using the index of desired gains of Pesek and Baker (PBI) in simultaneous improvement of several involved traits in wheat families. Peixoto et al (2021) noted that the classical index proposed by Smith and Hazel (SHI) and the sum of ranks index by Mulamba and Mock (MMI) were advantageous to produce sizeable gains distributed among several desired traits of biofortified lettuce, similar to that observed in Guimarães et al (2021) with rice and Ramos et al (2022) with peanut.…”
Section: Predicted Selection Gain From Index-based Selectionmentioning
confidence: 99%